2016
DOI: 10.1002/ijc.30467
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and risk of epithelial ovarian cancer in African American women

Abstract: Chronic inflammation has been implicated in the development of epithelial ovarian cancer (EOC); yet, the contribution of inflammatory foods and nutrients to EOC risk has been understudied. We investigated the association between the dietary inflammatory index (DII), a novel literature-derived tool to assess the inflammatory potential of one’s diet, and EOC risk in African American (AA) women in the African American Cancer Epidemiology Study (AACES), the largest population-based case-control study of EOC in AA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 52 publications
(88 reference statements)
3
49
1
Order By: Relevance
“…Given that the nutrient-based index scores are influenced by nutritional supplements use, 28,29 findings from these previous studies that are directly comparable to the current study results are from studies that calculated the nutrient-based index scores from food sources only (i.e., without including supplements). In a study conducted using data from the Iowa Women’s Health Study, there was a statistically significant 20% higher risk of colorectal cancer (HR: 1.20; 95% CI: 1.01–1.43) that became nonsignificant when supplements were excluded (HR: 1.12; 95% CI: 0.90–1.38).…”
Section: Discussionsupporting
confidence: 79%
“…Given that the nutrient-based index scores are influenced by nutritional supplements use, 28,29 findings from these previous studies that are directly comparable to the current study results are from studies that calculated the nutrient-based index scores from food sources only (i.e., without including supplements). In a study conducted using data from the Iowa Women’s Health Study, there was a statistically significant 20% higher risk of colorectal cancer (HR: 1.20; 95% CI: 1.01–1.43) that became nonsignificant when supplements were excluded (HR: 1.12; 95% CI: 0.90–1.38).…”
Section: Discussionsupporting
confidence: 79%
“…Twenty‐four articles were reviewed for full text . The summary statistics for each of these are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The summary statistics for each of these are presented in Table . Of those, 9 examined cancer incidence, 2 examined cancer mortality, and 13 examined odds of cancer in case–control studies . Additionally, 3 articles were published in 2014, 9 articles were published in 2015, and 12 were published in 2016 .…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional supplements influence DII scores given that the index is comprised mostly of nutrients; therefore, the source of dietary data for DII calculation (food sources and/or nutritional supplements) is important. Seven studies (four cohort [4446, 52] and three case-control [42, 47, 48]) examined the association of the DII with colorectal cancer risk during the period covered by this review. Overall, results were consistent that higher (more pro-inflammatory) DII scores were associated with higher risk of colorectal cancer; although there were differences based on whether the DII was calculated from food sources or from a combination of food and supplements.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that have derived separate DII scores with and without inclusion of supplements have found positive associations for DII scores with supplements and no association for DII scores from diet-only sources [46, 52]. For example, in the Iowa Women’s Health Study, Shivappa et al found a 20% higher risk of colorectal cancer (HR: 1.20; 95%CI: 1.01, 1.43) that became nonsignificant with the exclusion of supplements (HR: 1.12; 95%CI: 0.90, 1.38) [46].…”
Section: Resultsmentioning
confidence: 99%